Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s10495-023-01840-6
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as critical regulators and novel targets in cervical cancer: current status and future perspectives

Abstract: Cervical cancer is among the leading causes of cancer-associated mortality in women. In spite of vaccine availability, improved screening procedures, and chemoradiation therapy, cervical cancer remains the most commonly diagnosed cancer in 23 countries and the leading cause of cancer deaths in 36 countries. There is, therefore, a need to come up with novel diagnostic and therapeutic targets. Long non-coding RNAs (lncRNAs) play a remarkable role in genome regulation and contribute significantly to several devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 179 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Given that protein-coding genes constitute only 2% of the human genome, non-coding RNAs (ncRNAs), which are transcripts that do not code for any protein, are considered key regulatory molecules in all cellular processes ( Ranga et al, 2023 ). Among the ncRNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are potential biomarkers of PD ( Kuo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that protein-coding genes constitute only 2% of the human genome, non-coding RNAs (ncRNAs), which are transcripts that do not code for any protein, are considered key regulatory molecules in all cellular processes ( Ranga et al, 2023 ). Among the ncRNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are potential biomarkers of PD ( Kuo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common cancers in the female reproductive system, originating from the cervix. It is a serious threat to women’s health and is the most prevalent tumor in 23 countries [ 1 ]. CC has an incidence rate of 604,127 new cases and 341,831 deaths in 2020 as reported by the GLOBOCAN study.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA could act as competing endogenous RNA (ceRNA) to compete with cancer driver genes for microRNA (miR/miRNA) response elements [ 5 ]. According to recent studies, STARD7-AS1 has been identified as an autophagy-related lncRNA and has the potential to be an independent prognostic indicator in CC, as evidenced by the significant correlation between low STARD7-AS1 expression and poor survival outcome in patients with CC based on bioinformatics analysis (data from The Cancer Genome Atlas database) [ 6 7 8 ]. Moreover, STARD7, as the adjacent gene of STARD7-AS1, has been frequently explored in cancer development [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since STARD7 exerted a prominent role in various types of cancer, the function of its adjacent gene STARD7-AS1 in cancer development deserved further investigation. Despite STARD7-AS1, DBH-AS1 is also suspected as a lncRNA related to autophagy in CC [ 6 7 8 ]. DBH-AS1 has been widely investigated in various types of cancer.…”
Section: Introductionmentioning
confidence: 99%